Online Donation Information System with Payment Gateway - Adjie Krisnandy; Nurajijah Nurajijah (IJISTECH (International Journal of Information System and Technology), 2022)
The COVID-19 pandemic has had a significant impact on various aspects of social life. There is no exception in the aspect of religious activities in the process of receiving donations or raising funds which are still carried out manually by mosque officials. This is quite irrelevant to the current conditions that require to maintain health protocols in every activity. This study aims to design an Online Donation Information System with a Payment Gateway as an appropriate solution in accommodating the entire process of receiving donations and raising funds at mosques through electronic media. The method used is the scrum system development method with several stages such as product backlog, sprints, scrum meetings, and demos.